Implementing a system-wide cancer prehabilitation programme: The journey of Greater Manchester's 'Prehab4cancer'. (March 2021) - Moore, John; Merchant, Zoe; Rowlinson, Kirsty; McEwan, Karen; Evison, Matthew; Faulkner, Gemma; Sultan, Javed; McPhee, Jamie S.; Steele, James
Abstract: Patients undergoing major cancer interventions such as major surgical resection, chemotherapy, radiotherapy, and immunotherapy are prone to the adverse effects of their cancer, as well as to the side effects of the treatments designed to cure them. The Prehabilitation process supports cancer patients in preparing for the physiological challenges of their cancer treatments, whilst aiming to shorten recovery time, reduce peri-operative complications and improve compliance with non-surgical treatments. Prehabilitation will be most useful in older patients. Greater Manchester Integrated Care system is the first regional system in the UK to introduce delivery of system-wide, large scale physical activity supported multi-modal prehabilitation and recovery programme, Prehab4Cancer as a standard of care for cancer patients. It builds upon the successful implementation of Enhanced Recovery After Surgery + programme to improve surgical care in Greater Manchester. During this review we describe the journey to develop a system wide prehabilitation model for patients with cancer. Prehab4Cancer to date has focused on robust co-design, development, and implementation of an effective service model with attention paid to stakeholder engagement. This has led to receipt of high numbers of referrals from across Greater Manchester for the all the cancer groups involved. The successful implementation of the P4C pathway in GM presents a best practice model that might be adopted by other local and combined authority areas nationally.